RETRACTED: Environment care as Intention of non-business undergraduate students to enroll taxation courses - Simbillo Janus Aries Q.; Cordova Wilson; Gerona Estephany M. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001